Effecting Change on Studentsâ Critical Thinking in Problem Solving - Belecina, Rene R; Ocampo, Jr., Jose M (EDUCARE, 2018)
ABSTRACT: Critical thinking is the intellectually disciplined process of actively and skillsfully conceptualizing, applying, analyzing, synthesizing, and/or evaluating information gathered from, or generated by, observation, experience, reflection, reasoning, or communication, as a guide to belief and action. Most formal definitions of critical thinking characterize critical thinking as the intentional application of rational, higher order thinking skills, such as analysis, synthesis, problem recognition and problem solving, inference, and evaluation. Critical thinking and problem solving have long been important terminologies in the context of education, but within the framework of the 21st century classroom, they take on very specific definitions. Critical thinking employs higher level analytical skills to understand a problem and to work toward a means by which it can be solved, that word implies an answer. This study investigated the effect of using problem situations on the critical thinking of graduate students in solving problems. The study utilized the experimental design participated by a group of graduate students enrolled in Educational Statistics. Four problem situations were utilized that aimed to develop critical thinking of students in problem solving. Studentsâ critical thinking was measured before and after giving them the problem situations. Results revealed that studentsâ critical thinking in problem solving significantly improved after using problem situations. The students also expressed positive attitude and sentiments towards the used of these problem situations. It is recommended that these problems situations be used in other topics and areas in mathematics.Â Â Â Â Â Â Â KEY WORDS: Problem Situation; Critical Thinking; Problem Solving; Graduate Students; Positive Attitude and Sentiments.Â Â About the Authors: Rene R. Belecina, Ph.D. is a Full Professor at the CGSTER PNU (College of Graduate Studies and Teacher Education Research, Philippine Normal University) in Manila, Philippines. Jose M. Ocampo, Jr., Ph.D. is a Full Professor at the Faculty of Education Sciences PNU in Manila, the Philippines. The authors are able to be contacted via their e-mails at:Â rrbelecina@yahoo.com and juno_6970@yahoo.comSuggested Citation: Belecina, Rene R. & Jose M. Ocampo, Jr. (2018). âEffecting Change on Studentsâ Critical Thinking in Problem Solvingâ in EDUCARE: International Journal for Educational Studies, Volume 10(2), February, pp.109-118. Bandung, Indonesia and BS Begawan, Brunei Darussalam: Minda Masagi Press owned by ASPENSI and BRIMAN Institute, ISSN 1979-7877. Article Timeline: Accepted (December 19, 2017); Revised (January 20, 2018); and Published (February 28, 2018).